Teacher’s choice of english and vietnamese as classroom language in teaching grade 10 students speaking skills: a case study at a high school = lựa chọn ngôn ngữ lớp học của giáo viên trong dạy kỹ năng nói cho học sinh lớp 10 - Trần, Xuân Bình (2020)
Like the situation in many other high schools, English teachers at Le Hong Phong high school for the gifted in Nam Dinh are currently really concerned about non-English major students’ capability to communicate in English after graduation. As a result, use of English or Vietnamese as classroom language in teaching such communicative skills as speaking and listening are attracting increasing attentions from the teachers. Through observations, questionnaires and interviews with the two young English teachers and four grade 10 classes that they were in charge of, the researcher expected to explore the frequency and driving factors, as well as the students’ perceptions of the teachers’ use of English and Vietnamese as classroom language in teaching speaking skill. The case study has revealed that both teachers used English most of the time during speaking lessons and the reasons for their choice were mainly related to students’ proficiency improvement, favorable learning environment creation and speaking tasks. Meanwhile, Vietnamese was rarely used. In general, most of the students were satisfied with their teacher’s use of classroom language. Findings of this study provide a reference for teachers and authorities that are concerned about improving students’ communicative skills. Suggestions for future research on similar topics are given at the end of the paper.